STRUKTUR HUKUM ISLAM “STUDI PEMIKIRAN FAZLUR RAHMAN” - Mirwan (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
The legal aspect in Islam is closely related to the process of itsdetermination (istinbat al-ahkam) according to jurisprudents. In themethod of extracting Islamic law, the jurists, hierarchically, refer to alQur‘an, as-Sunnah, Ijma` (consensus) and Qiyas (analogy). However, theabove hierarchy is not fully used sequentially. In other words the jurorsare not in the same opinion how the application of the existing methods.Like the practice adopted by one of the contemporary Islamic thinkersFazlul Rahman.According to Fazlur Rahman, in interpreting the qur`an, it is appropriateto use a method called "double movement" that is the pattern ofpresentation as inductive reasoning and deductive reasoning. Rahmanpositioned the Sunnah of the Prophet as the highest precedent above thesunnah precedents of the Companions who were developing into ijma`(mutual agreement). Rahman viewed ijma` not to have the position asformalized by the ulama before, but to make ijma` that could accept theijtihad (interpretation) process using the Qiyas method (analogy).